Preparation method of epoxy allyl alcohol polyether
Through one-step reaction and adsorption treatment, the problems of complex traditional synthesis processes and long reaction cycles are solved, and the efficient preparation of epoxy-capped allyl alcohol polyether is achieved, improving production efficiency and product quality.
Patent Information
- Application Number
- CN202510068467.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, traditional synthesis processes are complex and have long reaction cycles, resulting in low production efficiency, high cost and insufficient resource utilization.
The one-step reaction method is adopted to anaerate the allyl alcohol polyether, alkali and epoxy capping agent under a nitrogen environment, and then add the adsorbent for adsorption treatment. The epoxy capping allyl alcohol polyether is obtained through a simple filtration step.
The reaction cycle is greatly shortened, the epoxy end capping rate reaches more than 90%, and the double bond retention rate reaches more than 97%, which simplifies the process flow, reduces production costs, and improves the purity and chemical stability of the product.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of allyl polyether preparation, and in particular to a method for preparing epoxy allyl alcohol polyether. Background Art
[0002] Epoxy-terminated polyether is a special chemical material. Its special feature is that the hydrogen on the hydroxyl group at the end of the polyether is replaced by an epoxy group. This structure gives this type of product lower viscosity, better flexibility and higher chemical reactivity compared to traditional polyethers. Due to the presence of epoxy groups, epoxy-terminated polyethers can react with compounds containing active hydrogen such as alcohols, amines, acids, etc., providing a wide range of chemical pathways for the synthesis of other compounds. This not only increases their application potential in different fields, but also makes this type of material play an irreplaceable role in certain specific applications. Epoxy-terminated allyl alcohol polyether is one of the important substances. It is a compound obtained by completely replacing the active hydroxyl groups in allyl alcohol polyether with epoxy groups. Compared with non-epoxy-terminated allyl alcohol polyether, epoxy-terminated polyether has more stable chemical properties and unique physical properties, which determine its special uses in multiple industries. It can be used as an additive to improve the performance of epoxy resin. In the fiber production process, it can be used as a solvent or catalyst to help improve production efficiency and fiber quality. In the plastic and rubber industries, it is used as a cross-linking agent or chain transfer agent to adjust the molecular weight and distribution of the polymer, thereby optimizing the performance of the final product. It provides good adhesion and wear resistance in coatings and inks and is suitable for various surface treatment needs. In electronics and electrical applications, it is used as an insulating material with excellent electrical properties and weather resistance. In construction and building materials, it enhances the strength and durability of building materials, especially for waterproofing and anti-corrosion treatment.
[0003] Despite this, the research and development of such products in China started late, and the overall technical level lags behind the international advanced level, especially in the preparation technology and quality control of high-end products. There is still a large gap. The types of glycidyl ether products produced in China are limited, and there is a certain gap in purity with similar foreign products, which not only affects the market competitiveness of the products, but also limits their use in high-end application fields. There are few research reports on allyl glycidyl ether products in China, resulting in insufficient market supply of related products, mainly relying on imports, especially in high-end application fields, with a high degree of dependence on products from countries such as Japan. This situation not only increases procurement costs, but may also be affected by changes in international trade policies. In addition, the traditional multi-step synthesis process is relatively complex, with a long reaction cycle, harsh reaction conditions, large equipment investment, high operating costs, and complex post-processing processes that increase production costs and reduce economic benefits. There is a certain waste in resource utilization in the existing production process, such as improper handling of by-products, low utilization of raw materials, and high energy consumption. Summary of the invention
[0004] In order to solve the problems of complicated traditional synthesis process and long reaction cycle in the prior art, the present application provides a preparation method of epoxy allyl alcohol polyether, wherein the present application puts allyl alcohol polyether and alkali into a reactor, heats up and adds epoxy capping agent, performs ripening reaction in nitrogen atmosphere, obtains a crude product after solid-liquid separation, adds adsorbent to the crude product for adsorption, and obtains epoxy capped allyl alcohol polyether after filtration. The present application adopts a one-step reaction, has a simple process, greatly shortens the reaction cycle, and the epoxy capping rate of the epoxy capped allyl alcohol polyether reaches more than 90%, and the double bond retention rate reaches more than 97%. Only adsorbent is needed for adsorption to make the epoxy capped polyether meet the index requirements.
[0005] The present application provides a method for preparing epoxy allyl alcohol polyether, comprising the following steps: S1, putting allyl alcohol polyether and alkali into a reaction kettle, heating up and adding epoxy capping agent, carrying out aging reaction under nitrogen environment, and separating solid and liquid to obtain a crude product after the reaction is completed; S2. Add an adsorbent to the crude product obtained in S1 for adsorption, remove monomers, and filter to obtain epoxy-terminated allyl alcohol polyether.
[0006] Furthermore, the allyl alcohol polyether in step S1 has a functionality of 1, a molecular weight of 300-1400, and a double bond retention rate of >90%.
[0007] Furthermore, the epoxy capping agent in step S1 is epichlorohydrin.
[0008] Furthermore, in step S1, the molar ratio of the allyl alcohol polyether to the epoxy capping agent is 1:1.05-2.0.
[0009] Furthermore, in step S1, the reaction temperature is 20-50° C., the reaction pressure is -0.08-0.3 MPa, and the aging reaction time is 2-4 h.
[0010] Furthermore, the base in step S1 is one or more of sodium hydroxide, potassium hydroxide and sodium hydride.
[0011] Furthermore, in step S1, the molar ratio of the allyl alcohol polyether to the base is 1:1.1-1.5.
[0012] Furthermore, the adsorbent described in step S2 is one or more of magnesium silicate, aluminum silicate, kaolin, magnesium aluminum silicate and diatomaceous earth, and the added amount is 1‰ to 10‰ of the total mass of the reactants.
[0013] Furthermore, in step S2, the temperature of the demonomerization is 100-110° C., the pressure is -0.1-0.08 MPa, and the demonomerization time is 2-4 hours.
[0014] Furthermore, the epoxy capping agent is recovered from the product of the monomer removal in step S2 through a liquid separation operation, and the recovered epoxy capping agent is returned to S1 for reuse.
[0015] In view of the problems existing in the prior art, the present application provides a preparation method, which adopts a one-step reaction and greatly improves production efficiency. The traditional multi-step synthesis process is not only time-consuming, complicated to operate, large in equipment investment, and high in operating cost. In contrast, the new one-step method only needs to put allyl alcohol polyether and alkali into a reactor, heat up and add an epoxy end-capping agent, perform a aging reaction under a nitrogen environment, and obtain a crude product after centrifugal solid-liquid separation. Add an adsorbent to the crude product for adsorption treatment, and the finished product can be obtained after filtering. The synthetic core of the epoxy-terminated allyl alcohol polyether is to convert the hydroxyl group at the end of the allyl alcohol polyether into an epoxy group. This process involves a nucleophilic substitution reaction between allyl alcohol polyether and an epoxy end-capping agent under alkaline conditions. The alkaline substance acts as a catalyst to promote the attack of the hydroxyl group on the epoxy end-capping agent, generate a new epoxy structure and release a by-product chloride.
[0016] In terms of post-processing, compared with the cumbersome steps of multiple washing, concentration and drying required in the traditional process, the new method only requires the simple addition of an adsorbent for adsorption treatment, and then filtration to obtain the finished product. This improvement not only saves a lot of time and labor costs, but also reduces the risk of product deterioration due to long-term exposure to air. The de-monomerization process further improves the purity of the product, and the effluent can be recycled and reused through liquid separation operations, realizing the effective recycling of resources, helping to reduce production costs and improve economic benefits.
[0017] The product obtained in this application ensures a high epoxy end-capping rate and double bond retention rate, which is crucial for maintaining the chemical stability and activity of the product. The generated end-epoxy allyl alcohol polyether has both good flexibility and high chemical activity. This structural feature makes the product excellent in various application scenarios, especially in coatings and inks that require good adhesion, wear resistance and weather resistance, and in building materials that require high strength and durability. The preparation method of this application improves the purity of the product. By introducing adsorbents such as magnesium silicate, aluminum silicate, etc., impurities generated during the reaction, including unreacted monomers and other by-products, can be effectively removed, thereby ensuring the high quality of the final product. The choice of adsorbent not only takes into account its adsorption effect, but also takes into account environmental friendliness and recyclability. The de-monomerization process further improves the purity of the product, and the effluent is recycled and reused through liquid separation operation, realizing the effective recycling of resources.
[0018] In summary, the preparation method proposed in this application simplifies the process flow, optimizes the reaction conditions, improves the product purity, and reduces the complexity of the post-processing steps. The epoxy end-capping rate and double bond retention rate of the product are improved, and the chemical stability and activity are enhanced. The simplified process flow and reduced post-processing steps not only improve production efficiency and reduce costs, but also promote the effective use of resources and environmental protection. DETAILED DESCRIPTION
[0019] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.
[0020] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.
[0021] Example 1 S1. Add 338.82g of all-EO allyl alcohol polyether with a molecular weight of 300.11 and 41.22g of sodium hydride with a content of 98.6% into a four-necked bottle, open the nitrogen valve to pass nitrogen, start stirring, add 211g of epichlorohydrin with a content of 99% at 25°C, add for 2.5h, keep the dropping temperature at 20-30°C, carry out aging reaction for 2h after the addition is completed, keep the temperature at 30-33°C, centrifuge the obtained reaction product for 30min, and separate 461.33g of organic phase crude product.
[0022] S2, add the crude product obtained in S1 to a four-necked bottle, stir with nitrogen, add 100 mesh magnesium silicate and aluminum silicate, the addition amount is 2‰ of the mass of the crude product obtained in S1, heat to 80°C for adsorption for 2h, continue to heat to 100°C to start vacuuming, strip monomers, the pressure is -0.1MPa, the strip monomer time is 2h, remove excess epichlorohydrin and water, and return to step S1 for repeated use. When the moisture content is <0.05%, 342.15g of product is obtained by filtration, and the yield is 85.09%.
[0023] Product indicators: viscosity is 20mPa.S (25℃), sodium ion content is 1ppm, pH is 7.63, moisture content is 0.032%, acid value is 0.015mgKOH / g, color value is 49APHA, epoxy value is 0.2583mol / kg, epoxy end-capping rate is 91.99%, unsaturated value is 2.7234mol / kg, double bond retention rate is 97.00%, and base value CPR is 1.5ppmKOH.
[0024] Example 2 S1. Add 426.59g of all-EO allyl alcohol polyether with a molecular weight of 400.14 and 66.12g of potassium hydroxide with a content of 99.5% into a four-necked bottle, open the nitrogen valve to pass nitrogen, start stirring, warm to 30 ° C and add 104.62g of epichlorohydrin with a content of 99%, add it dropwise for 1.5h, and the dropping temperature is maintained at 30-42 ° C. After the addition is completed, the aging reaction is carried out for 3h, and the temperature is maintained at 32-39 ° C. The resulting reaction product is centrifuged for 30min to separate 466.26g of organic phase crude product.
[0025] S2, add the crude product obtained in S1 to a four-necked bottle, stir with nitrogen, add clay and aluminum magnesium silicate, the addition amount is 3‰ and 2‰ of the crude product mass obtained in S1 respectively, heat to 80℃ for adsorption for 2h, continue to heat to 100℃ to start vacuuming, strip monomer, pressure is -0.08MPa, strip monomer time is 4h, remove excess epichlorohydrin and water, and return to step S1 for repeated use. 412.06g of product was obtained by filtration when the moisture content was <0.05%, and the yield was 84.72%.
[0026] Product indicators: viscosity is 35mPa.S (25℃), potassium ion content is 2ppm, pH is 7.25, moisture content is 0.035%, acid value is 0.015mgKOH / g, color value is 28APHA, epoxy value is 0.2041mol / kg, epoxy capping rate is 93.11%, unsaturated value is 2.1485mol / kg, double bond retention rate is 98.02%, and base value CPR is 1.2ppmKOH.
[0027] Example 3 S1. Add 525.19g of all-EO allyl alcohol polyether with a molecular weight of 524.96 and 45.23g of sodium hydroxide with a content of 97.33% into a four-necked bottle, open the nitrogen valve to pass nitrogen, start stirring, warm to 35 ° C and add 185.2g of epichlorohydrin with a content of 99%, add it dropwise for 1h, and the dropping temperature is maintained at 32-40 ° C. After the addition is completed, the aging reaction is carried out for 3h, and the temperature is maintained at 40-42 ° C. The resulting reaction product is centrifuged for 30min with a centrifuge to separate 657.02g of organic phase crude product.
[0028] S2, add the crude product obtained in S1 to a four-necked bottle, stir with nitrogen, add 100 mesh magnesium silicate, aluminum silicate and diatomaceous earth, the addition amount is 3‰, 2‰ and 1‰ of the crude product mass obtained in S1 respectively, heat to 80℃ for adsorption for 2h, continue to heat to 110℃ to start vacuuming, strip monomer, pressure is -0.1MPa, strip monomer time is 3h, remove excess epichlorohydrin and water, can return to step S1 for repeated use. Filter to obtain 500g of product when moisture <0.05%, the yield is 86.02%.
[0029] Product indicators: viscosity is 44mPa.S (25℃), sodium ion content is 1ppm, pH is 7.43, moisture content is 0.037%, acid value is 0.017mgKOH / g, color value is 66APHA, epoxy value is 0.1618mol / kg, epoxy end-capping rate is 94.02%, unsaturated value is 1.6963mol / kg, double bond retention rate is 98.56%, and base value CPR is 1.6ppmKOH.
[0030] Example 4 S1. Add 506.6g of PO / EO=75 / 25 allyl alcohol polyether with a molecular weight of 1013.18 and 26.71g of sodium hydroxide with a content of 97.33% into a four-necked bottle, open the nitrogen valve to pass nitrogen, start stirring, warm to 40°C and add 69.43g of epichlorohydrin with a content of 99%, add for 1h, keep the dropping temperature at 40-50°C, carry out aging reaction for 4h after the addition is completed, keep the temperature at 45-50°C, centrifuge the obtained reaction product for 30min, and separate 533.78g of organic phase crude product.
[0031] S2, add the crude product obtained in S1 to a four-necked bottle, stir with nitrogen, add 100 mesh magnesium silicate, magnesium aluminum silicate and diatomaceous earth, the addition amount is 4‰, 2‰ and 1‰ of the mass of the crude product obtained in S1 respectively, heat to 80℃ for adsorption for 2h, continue to heat to 110℃ to start vacuuming, strip monomer, pressure is -0.08MPa, strip monomer time is 3h, remove excess epichlorohydrin and water, can return to step S1 for repeated use. Filter to obtain 484.84g of product when the moisture content is <0.05%, and the yield is 90.69%.
[0032] Product indicators: viscosity is 106mPa.S (25℃), sodium ion content is 1ppm, pH is 7.23, moisture content is 0.027%, acid value is 0.019mgKOH / g, color value is 85APHA, epoxy value is 0.0868mol / kg, epoxy end-capping rate is 92.83%, unsaturated value is 0.9238mol / kg, double bond retention rate is 98.78%, and base value CPR is 2.3ppmKOH.
[0033] Example 5 S1. Add 1227.53g of PO / EO=67 / 33 allyl alcohol polyether with a molecular weight of 1407.07 and 43g of sodium hydroxide with a content of 97.33% into a four-necked bottle, open the nitrogen valve to pass nitrogen, start stirring, heat to 40°C and add 85g of epichlorohydrin with a content of 99%, add for 1h, keep the dropping temperature at 40-50°C, carry out aging reaction for 4h after the addition is completed, keep the temperature at 48-50°C, centrifuge the obtained reaction product for 30min, and separate 1347.71g of organic phase crude product.
[0034] S2, add the crude product obtained in S1 to a four-necked bottle, stir with nitrogen, add 100 mesh magnesium silicate, aluminum silicate and diatomaceous earth, the addition amount is 4‰, 5‰ and 1‰ of the mass of the crude product obtained in S1 respectively, heat to 90℃ for adsorption for 2h, continue to heat to 110℃ to start vacuuming, strip monomer, pressure is -0.1MPa, strip monomer time is 2h, remove excess epichlorohydrin and water, can return to step S1 for repeated use. 1149.29g of product is obtained by filtration when the moisture content is <0.05%, and the yield is 90.04%.
[0035] Product indicators: viscosity is 160mPa.S (25℃), sodium ion content is 3ppm, pH is 7.60, moisture content is 0.047%, acid value is 0.011mgKOH / g, color value is 100APHA, epoxy value is 0.0636mol / kg, epoxy end-capping rate is 93.12%, unsaturated value is 0.6774mol / kg, double bond retention rate is 99.10%, and base value CPR is 3.1ppmKOH.
Claims
1. A method for preparing epoxy allyl alcohol polyether, characterized in that: The following steps are involved: S1, putting allyl alcohol polyether and alkali into a reactor, heating and adding epoxy end-capping agent, performing aging reaction under nitrogen environment, and separating solid and liquid after the reaction to obtain a crude product, wherein the molar ratio of the allyl alcohol polyether to the epoxy end-capping agent is 1:1.05-2.0, and the molar ratio of the allyl alcohol polyether to the alkali is 1:1.1-1.5; S2. Add an adsorbent to the crude product obtained in S1 for adsorption, remove monomers, and filter to obtain epoxy-terminated allyl alcohol polyether.
2. The method for preparing an epoxy allyl alcohol polyether according to claim 1, characterized in that: The allyl alcohol polyether in step S1 has a functionality of 1, a molecular weight of 300-1400, and a double bond retention rate of >90%.
3. The method for preparing an epoxy allyl alcohol polyether according to claim 2, characterized in that: The epoxy capping agent in step S1 is epichlorohydrin.
4. The method for preparing an epoxy allyl alcohol polyether according to claim 1, characterized in that: The aging reaction temperature in step S1 is 20-50° C., the reaction pressure is -0.08-0.3 MPa, and the reaction time is 2-4 hours.
5. The method for preparing an epoxy allyl alcohol polyether according to claim 1, characterized in that: The alkali in step S1 is one or more of sodium hydroxide, potassium hydroxide and sodium hydride.
6. The method for preparing an epoxy allyl alcohol polyether according to claim 1, characterized in that: The adsorbent described in step S2 is one or more of magnesium silicate, aluminum silicate, kaolin, magnesium aluminum silicate and diatomaceous earth, and the added amount is 1‰ to 10‰ of the mass of the crude product obtained in S1.
7. The method for preparing an epoxy allyl alcohol polyether according to claim 1, characterized in that: The demonomerization temperature in step S2 is 100-110° C., the pressure is -0.1-0.08 MPa, and the demonomerization time is 2-4 hours.
8. The method for preparing an epoxy allyl alcohol polyether according to claim 1, characterized in that: In step S2, the epoxy capping agent is recovered from the product of the monomer removal by liquid separation operation, and the recovered epoxy capping agent is returned to S1 for reuse.
Citation Information
Cited By
Novel diallyl-terminated polyether as well as synthesis method and application thereof
CN120965986A